Hidrología y variación topográfica de un riachuelo subantártico en la ensenada MacKellar, Isla Rey Jorge, Antártida - Tavares Correa, Carlos (2005)
The purpose of this study is to present preliminary results of the hydrologic and topographic monitoring of a small stream at the King George Island, Antarctica. Two methods were used in order to measure stream discharge: an area-velocity method using a flow meter and a Parshall flume. Also a topographical survey was made using a total-station theodolite. Great stream discharge fluctuations were identified at the seven stream sections between January 21st and February 13th, 2000. Comparison between 1999 and 2000 topographic survey showed a volumetric decreasing of about 9.450 m3 in one year. This topographic variation could be explained by the erosive capacity of the maximum discharges occurred during the beginning of the australsummer, when a new channel was built.